The Effect Of Cost Reduction Strategy On Improving Business Performance In Coffee Msmes In Pasuruan Regency - Tama, Wahana Sari Yudha (International Economic Conference of Business and Accounting, 2024)
This study investigates the effect of cost reduction strategies on the business performance of coffee micro, small, and medium enterprises (MSMEs) in Pasuruan Regency, East Java, Indonesia. The cost reduction strategy is one of the strategies that is widely applied by MSME managers when facing a recession due to the Covid-19 pandemic. The implementation of this strategy aims to ensure that the business is run, can survive, and still generate profits. However, the implementation of cost reduction that is carried out without consideration will also affect business performance, therefore this study is important to find out the effect of cost reduction on business performance. So that MSMEs that implement this strategy can improve their business performance. This study uses a quantitative method using a structured questionnaire to collect data from 50 coffee SME owners/managers. The data was analyzed using SmartPLS to test the hypothesis that cost reduction strategies have a positive impact on business performance. These findings show a significant positive correlation between cost reduction and business performance, which shows that cost reduction strategies are effective in improving business performance in coffee SMEs in Pasuruan Regency. The study concludes that coffee SMEs should prioritize effective cost reduction strategies to improve their business performance, especially in aspects such as production costs, labor costs, and overhead costs.